Connecting Storytelling and Social Wellness: A Case for Holistic Storytelling in the Elementary Classroom (LEARNing Landscapes, 2017)
Storytelling has a fundamental place in teaching practice, most noticeably in the sharing and developing of curricular content. But teachers share more than academic content with children. A critical prerequisite for meaningful, engaged learning is a strong sense of community and social wellness in the classroom. Based on an inquiry into literature and reflection on personal practice, this study asserts that the practice of storytelling fosters social wellness in the classroom and supports the healthy development of each child as a whole human being within and as part of that community. Connecting storytelling and social wellness, this inquiry offers a unique definition of “holistic storytelling.”
Keywords: teaching; storytelling; social wellness; healthy development; holistic storytelling